(untitled) (Third Sector Social Economic Review, 2023)
As a management approach that emerged in the private sector, Total Quality Management started to be implemented in the public sector in the 1980s. Since the 1990s, higher education institutions have also adopted and implemented the quality management approach. In the Turkish higher education system, quality management studies started to be implemented with the Bologna Process carried out in 1999. Quality management studies have been carried out since 2005 to cover all universities. In this study, it is aimed to reveal how the employees involved in quality management studies at universities evaluate the quality management process, which consists of preparation, implementation and evaluation stages. For this purpose, a questionnaire, one of the quantitative research techniques, was used in the research. The population of the research consists of personnel participating in quality management studies at all state and foundation universities in Turkey. In this context, a survey link was sent to all state and foundation universities (129 state-74 foundation) in Turkey, and a total of 346 people from 99 state and 39 foundation universities responded. The obtained data were transferred to SPSS Windows version 24 and analyzed. It has been determined that the personnel involved in quality management studies at universities evaluate the quality management process as ’successful’. On the other hand, it has been observed that there is a statistically significant difference between the age, title, the type of university where the participants work, the period of establishment and voluntary participation in quality management studies, and the evaluations related to the quality management process. How employees evaluate the quality management process is very important in the placement and implementation of quality management in universities. Because quality management takes place in three dimensions: human-process-customer. People are one of the most important dimensions of quality management. Employees who carry out these studies in universities are expected to have knowledge of the approach, to receive continuous and systematic training, and to internalize the quality culture.